Distribution of genetic polymorphisms in drug metabolizing gene CYP2C9 in type 2 diabetes population. - Sapkota, Alisha (2021)
ABSTRACT: Background: Diabetes is common in Nepalese population and oral hypoglycemic drugs are used for treatment, there are no data regarding genetic polymorphisms of drugs metabolizing genes that effects the efficacy of used drugs in our context. This study is framed to determine the presence of genetic polymorphisms in CYP2C9 gene in the people suffering from Type 2 Diabetes Mellitus. Since the polymorphism of drug metabolizing gene CYP2C9 is responsible for altered efficacy of commonly used sulponylureas drugs. This study can be crucial for therapeutic response of drugs and also to prevent adverse drug reactions like hypoglycemia. Objectives: This study was designed with the aim to observe the frequency of CYP2C9 polymorphisms in Type 2 DM patients and healthy controls. Method and methodology: It was a cross-sectional study conducted in Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal from July 2021 to December 2021. 43 patients diagnosed with Type 2 Diabetes Mellitus visiting Medical OPD and 43 healthy controls who have come for health checkup in General Health Checkup (GHC) of TUTH were included in the study. EDTA samples were collected from study subjects and analyzed for HbA1c and for molecular analysis of CYP2C9 gene polymorphism using PCR-CTPP method. Results: The genotype frequency of CYP2C9 gene was 93% for wild type homozygous CYP2C9 *1/* and 7% for heterozygous CYP2C9 *1/*3. Variant type homozygous CYP2C9 *3/*3 was not found in our study. The allele frequency of CYP2C9 *1 was 96.3% and CYP2C9* was 3.7%. Genotype distribution and allele frequency of CYP2C9 was not significantly different among controls and Type 2 Diabetic a patients. Patients with CYP2C9*1/*3 genotype were found to have better glycaemic control than wild-type homozygotes CYP2C9 *1/*1. Conclusion: Results showed that there are variations within the CYP2C9 alleles and genotype frequencies in Nepalese population. Type 2 DM patients with CYP2C9*3 alleles had better glycemic control compared to those with CYP2C9 *1 alleles which might be linked to decrease enzymatic activity of sulphonylureas by CYP2C9*3 alleles. keywords: CYP2C9, Type 2 Diabetes Mellitus, Sulphonylureas, PCR-CTPP